Mathematical prerequisites for non-STEM programs - Rohenroth, Dunja; Neumann, Irene; Heinze, Aiso (Frontiers in Education, 2023)
Mathematics is applied in a broad range of academic disciplines and thus takes on a paramount role for college access. However, students often take for granted the necessity of mathematics for STEM subjects but are unaware of or insufficiently informed about the role of mathematics for subjects outside of STEM. In fact, there is no in-depth empirical investigation on which mathematical prerequisites are expected by university instructors from incoming non-STEM undergraduates. The present paper addresses this research gap. We conducted a three-round Delphi study with N = 19/547/337 university instructors in Germany teaching undergraduates in non-STEM programs. Our results show that many more subjects require mathematical knowledge than is commonly assumed. We present a comprehensive catalogue of mathematical prerequisites that students are expected to have at the beginning of their studies. The prerequisites include (1) mathematical content, (2) mathematical processes, (3) views about the nature of mathematics, and (4) personal characteristics. The expected mathematical prerequisites primarily address a basic understanding and do not require formalistic or abstract mathematical knowledge and skills. The Delphi study also revealed five subject groups in which similar mathematical prerequisites are expected. Although the study’s focus is on German instructors, it provides valuable insights for an international audience as well. For example, future research can use our results to adapt instruments to explore predictors of college success. In addition, our results inform stakeholders involved in the transition from high school to college and in college education, such as teachers preparing their students for future study, college instructors making their expectations transparent to incoming students, and policymakers involved in curriculum design.